Preparation of mozzarella Cheese using Skim Milk Filled with Coconut Milk - Gnana Selva Johnson (Department of Dairy Science, College of Veterinary and Animal Sciences, 1994)
A detailed study was carried out to determine the quality of coconut fat filled milk for the preparation of Mozzarella cheese and why drinks. Literatures based on filled milk products has been reviewed, apart from the preparation of cheese and why drinks. The control samples of Mozzarella cheese and whey drinks were prepared using cow’s milk. Experiment I products were prepared from milk in which 50 per cent of milk fat was replaced with coconut fat. Experiment II products were prepared from cheese milk in which 100 per cent of milk fat was replaced with coconut fat. All the samples of milk were standardized to 4 per cent fat. A total of 6 trials were carried out to obtain reliable data for statistical analysis. The acidity, pH, stretchbility and FDM content were found to be similar in control, experiment I and II Mozzarella cheese. Eventhough, the control Mozzarella cheese were found to have slightly higher yield protein, fat and lower moisture content, the experimental I and II. Mozzarella cheese also satisfied the requirements for good quality Mozzarella cheese. The control Mozzarella cheese got maximum score on sensory evaluation than the experiment I and II Mozzarella cheese. Pineapple and Lemon falvoured control, experiment I and II whey drinks were found to be equally acceptable with nodifference on storage studies ar 5 + loC. Total bacterial count on whey drinks were also made. The studies revealed that the cow milk in which the milk fat replaced to the extend of 50 per cent and 100 per cent with coconut fat can be effectively utilised for preparation of Mozzarella cheese. The quality of such cheese is comparable with that made from cow milk.